P-230 Senescence in mammalian embryos as a novel assay for quality control in the IVF laboratory. (30th June 2022) - Schenkman, E; Russell, H; Lattanzio, F; Angle, M; Swain, J
Abstract: Study question: Can senescence biomarkers be used as a more sensitive assay for IVF laboratory quality control than a conventional mouse embryo assay (MEA)? Summary answer: Senescence biomarkers are more sensitive than a MEA and should be considered as a novel quality control assay in assessing overall IVF laboratory environment. What is known already: An MEA is a bioassay that is utilized to detect toxicity and suboptimal conditions, but only assesses the ability of the embryos to develop to the blastocyst stage. The majority of human embryos created during IVF do not result in a live birth, most either arrest or degenerate. Suboptimal culture conditions and accompanying environmental stressors may be responsible or some of this lack of embryo development. Senescence or developmental arrest, like apoptosis, is a defensive mechanism that halts further development of stress, poor quality or abnormal embryos. Senescence should be considered a possible reason for a high embryos loss rate. Study design, size, duration: Murine zygotes from the strain B6 C3 F1 x B6 D2 F1 (N = 263) were exposed to 12.5nM Doxorubicin (DOX), a known inducer of senescence as a positive control, either 250nM or 500nM H2 O2 or atmospheric oxygen conditions (20%) to mimic oxidative stress. These treatment groups were compared to embryos cultured without H2 O2 in a low oxygen (5% 02 ) environment. The zygotes were cultured for 72 hours, and biomarkers of senescence were assessed. Participants/materials, setting, methods: Embryos were assessed at 72 hours with a confocal microscope (Zeiss) and blastocyst conversion rate and number of cells/blastocyst was calculated. The following senescence markers were examined, SAβ-gal (SPiDER-β-Gal), IL-6 mRNA (RT-qPCR) and CellRox Deep Red, a fluorogenic reactive oxygen species (ROS) indicator was also evaluated. Fiji Image J software was used to calculate Corrected Total Cell Fluorescence (CTCF) as a percentage of the low oxygen group and GraphPad Prism was used for data analysis. Main results and the role of chance: When comparing the blastocyst conversion rate, all treatment groups showed a blastocyst conversion rate of > 80% after 72 hours of exposure, indicating that all would have "passed" assessment with a conventional MEA (p > 0.05). However, when the average number of cells per blastocyst was compared to the low oxygen group, all groups had a significantly lower average number of cells per blastocyst (112±26.65 for low oxygen, 74±7.95 for high oxygen, 82± 24.54 for 500 nM H2 O2, 89 ± 34 for 250 nM H2 O2 and 63± 20.01 for 12.5 nM DOX, p < 0.05). All of the treatment groups had a significant increase in the relative fold change of IL-6 mRNA compared to the low oxygen environment (2.2 for the high oxygen, 2.5 for 500 nM H2 O2, 2.9 for 250 nM H2 O2, and 7.4 for 12.5 nM DOX, p < 0.05). The CTCF for SAβ-Gal using the SPIDER-β- Gal assay was significantly elevated in all treatment groups (145% for high oxygen, 162% for H2 O2 250 nM, 193% for 12.5 nM DOX and 196% for 500 nM H2 O2, p < 0.05). A significant increase in the CTCF for CellRox Deep Red was also observed (289% for 12.5 nM DOX, 492% for 250 nM H2 O2, 763% for 500 nM H2 O2, and 925% for high oxygen, p < 0.05). Limitations, reasons for caution: This analysis is currently limited by the lack of a specific senescence marker. This approach is also invasive, destroying the embryo, not lending itself to clinical human embryo selection. Although the mouse model has advantages, translating these results into human embryos is a limitation of this study. Wider implications of the findings: This optimized novel assay can be used to provide great insight about the subtle laboratory culture/environmental conditions in the IVF laboratory. The results support the hypothesis that environmental stressors can induce senescence biomarkers and implicate their participation in the degeneration of previously viable embryos. Trial registration number: not applicable